Analisis Keandalan Laporan Keuangan dalam Penerapan Cloud Accounting - Aulia Shancai Dwi Arini; Sifera Patricia Maithy (Jurnal Riset Akuntansi, 2025)
The development of information technology has driven a transformation in the accounting system, one of which is through the implementation of cloud accounting. This system provides ease of access, efficiency, and real-time data updates. However, questions regarding the reliability of the financial reports produced remain. This article aims to analyze the extent to which the cloud accounting system can produce reliable financial reports, taking into account aspects of data security, input quality, system integration, and compliance with accounting standards. This research was conducted by conducting a literature study of various academic literature and related regulations. The results of the analysis show that cloud accounting has great potential to improve the reliability of financial reports, as long as it is supported by a reliable security system, adequate internal control, and high user competence. This article also identifies the challenges and opportunities that arise from the implementation of cloud accounting in financial reporting, as well as its implications for the audit process in the digital era.